Impacts of initial ICU driving pressure on outcomes in acute hypoxemic respiratory failure: a MIMIC-IV database study - ChunMei Xie; WenYi Tang; JiaYuan Leng; Ping Yang; Yan Zhang; Shu Wang (Scientific Reports)
Abstract Driving pressure (DP) is a marker of severity of lung injury in patients with acute respiratory distress syndrome (ARDS) and has a strong association with outcome. However, it is uncertain whether limiting DP can reduce the mortality of patients with acute hypoxemic respiratory failure (AHRF). Therefore, this study aimed to determine the correlation between the initial DP setting and the clinical outcomes of patients with AHRF upon their initial admission to the intensive care unit (ICU). The Medical Information Mart for Intensive Care IV (MIMIC-IV) database was used to search the data of patients with AHRF, with 180-day mortality representing the primary outcome. Multiple regression analysis was subsequently performed to evaluate the initial DP and 180-day mortality association. The reliability of the results was validated using restricted cubic splines and interaction studies. This study retrospectively analyzed data from 907 patients—581 (64.06%) in the survival group and 326 (35.94%) in the nonsurvival group (NSG)—who were followed up 180 days after admission. The results revealed that an elevated initial DP was significantly correlated with 180-day mortality (HR 1.071 (95% CI 1.040, 1.102)), especially when the initial DP exceeded 12 cmH2O. AHRF patients with an initial DP > 12 cmH2O had significantly greater mortality at 28 days (p = 0.0082), 90 days (p = 0.0083), and 180 days (p = 0.0039) than those with an initial DP ≤ 12 cmH2O. Among severe patients with AHRF, 180-day mortality was significantly greater in the group with an initial DP > 12 cmH2O than in the group with an initial DP ≤ 12 cmH2O (p = 0.029). The hospital length of stay (LOS) for patients with an initial DP < 12 cmH2O was significantly longer than that for those with an initial DP > 12 cmH2O (p = 0.029). Among patients with AHRF and an initial DP > 12 cmH2O, the survival group had a significantly longer LOS in the ICU than the NSG (p = 0.00026). The initial DP settings were correlated with 180-day mortality among patients with AHRF admitted to the ICU. Particularly for patients with AHRF, it is crucial to consider implementing early restrictive DP ventilation as a potential means to mitigate mortality, and close monitoring is essential to evaluate its impact.